New technologies in the management of overactive bladder: current research and future prospects - Marinkovic, Serge P. (Ther Adv Urol, 2019)
Overactive bladder is characterized by frequency, urgency (wet or dry) and nocturia. These troublesome symptoms incur both a physiologic and economic cost, expected to be in excess of US$82 billion in the USA and Europe by the year 2020. Second-tier medicinal oral therapies for overactive bladder abound, but the failure rate or discontinuation at 1 year exceeds 50%. Tertiary-tier therapies involve surgical alternatives including neuromodulation of sacral nerve 3 (S(3)) or the posterior tibial nerve as a means to manipulate and ameliorate the above-described voiding symptoms. Sacral neuromodulation has been studied for more than 20 years, but newer, smaller, rechargeable implantable devices are in the forefront of current investigation. Hopes are that modifications to the device will eventually be possible at the patient’s home, rather than the physician’s office, with close urological/gynecologic supervision and guidance. Another means of surgical intervention for overactive bladder includes the use of a cystoscopy-guided radiofrequency probe by which energy disrupts the bladder floor neural voiding plexi. Stem cell therapy is also being evaluated for overactive bladder but is in the early stages of development.